Fiber-reinforced regenerated polypropylene composite material and preparation method thereof

The method enhances wear resistance and flame retardancy in fiber-reinforced recycled polypropylene composites by modifying fibers through single-molecule self-assembly and carbon deposition, followed by high-temperature and high-pressure treatment, and electron beam irradiation to create cross-linked polypropylene.

CN119192733AInactive Publication Date: 2024-12-27ANHUI GUANHONG PLASTIC IND

Patent Information

Application Number
CN202411726195.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-28
Publication Date
2024-12-27
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

Existing fiber-reinforced recycled polypropylene composites suffer from inadequate wear resistance and flame retardancy due to incomplete coating of continuous long glass fibers and weak interfacial bonding strength.

Method used

A method involving the preparation of modified fibers through single-molecule self-assembly and carbon deposition, followed by high-temperature and high-pressure treatment, combined with electron beam irradiation to create cross-linked polypropylene, enhancing the material's wear resistance and flame retardancy.

Benefits of technology

The method significantly improves wear resistance and mechanical properties by promoting β-crystal formation and carbonization, resulting in a densified structure with enhanced flame retardancy.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119192733A_ABST
    Figure CN119192733A_ABST
Patent Text Reader

Abstract

The invention discloses a fiber-reinforced regenerated polypropylene composite material and a preparation method thereof, and belongs to the technical field of polypropylene processing, the fiber-reinforced regenerated polypropylene composite material comprises the following raw materials by weight: 80-100 parts of cross-linked polypropylene resin, 10-20 parts of modified fiber, 10-20 parts of a plasticizer, 2-5 parts of a stabilizer, 0.5-2 parts of a lubricant and 0.5-1 part of an antioxidant; the modified fiber and the radiation cross-linking agent are prepared, in the melting process, the modified fiber promotes heterogeneous nucleation of regenerated polypropylene to form a beta crystal form, the radiation cross-linking efficiency is improved, the wear resistance of the material is enhanced, a phosphoric acid component in the radiation cross-linking agent is decomposed during combustion to generate an acidic substance, and the flame retardance of the material is improved. Carbonization of a triazine ring on the surface of the modified fiber is promoted, so that a rough carbon structure is formed on the surface of the modified fiber, the flowability of a combustion material is reduced, and the structure and a carbon layer on the surface of silicon carbide are synergistically matched to remarkably improve the flame retardant property of the composite polypropylene.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of polypropylene processing, and in particular to a fiber-reinforced recycled polypropylene composite material and a preparation method thereof. Background Art

[0002] In order to improve the wear resistance and flame retardancy of recycled polypropylene, technological research and development has entered a new stage. In order to enhance wear resistance, glass fiber or carbon fiber is usually added. These fiber materials can greatly improve the hardness and wear resistance of polypropylene, and are suitable for automotive parts, industrial equipment and other fields that require high wear resistance. In terms of enhancing flame retardancy, researchers introduce flame retardants and natural fibers, such as hemp fibers, to further improve the stability of the material in high temperature environments. It is not only more stable and durable, but also has higher safety. It is widely used in construction, home furnishings, industrial production and other fields.

[0003] Prior art CN116218075A discloses a long glass fiber reinforced recycled polypropylene material with low volatile organic matter characteristics and a preparation method thereof, comprising the following raw material composition in weight percentage: 12-62% polypropylene resin, 10-30% recycled polypropylene, 20-50% continuous long glass fiber, 4% compatibilizer, 2% antioxidant and 2% lubricant.

[0004] The above-mentioned patent content achieves the desired technical effect by introducing continuous long glass fibers, polypropylene resin and other auxiliary materials into recycled polypropylene. However, since only the coating method is used in the process of surface modification of the continuous long glass fibers, it is easy to cause incomplete coating of the modified layer. Furthermore, since the polarity of the surface of the continuous long glass fibers is quite different from that of organic materials such as polypropylene resin, it will also lead to weak interfacial bonding strength, and the wear resistance of the material needs to be further improved.

[0005] In view of the technical defects in this aspect, a solution is now proposed. Summary of the invention

[0006] The object of the present invention is to provide a fiber-reinforced recycled polypropylene composite material and a preparation method thereof, so as to solve the technical problem that the wear resistance and flame retardancy of the fiber-reinforced polypropylene composite material in the prior art need to be further improved.

[0007] The object of the present invention can be achieved by the following technical scheme: A fiber-reinforced recycled polypropylene composite material, comprising the following raw material compositions by weight: 80-100 parts of cross-linked polypropylene, 10-20 parts of modified fiber, 10-20 parts of plasticizer, 2-5 parts of stabilizer, 0.5-2 parts of lubricant and 0.5-1 parts of antioxidant;

[0008] Wherein, the preparation method of cross-linked polypropylene comprises the following steps:

[0009] A1, mixing recycled polypropylene, modified fiber and radiation crosslinking agent uniformly and adding them into a twin-screw extruder, and melt-extrude to obtain a polypropylene substrate;

[0010] Reaction principle for preparing polypropylene substrate: During the high-temperature melting process, the amide groups on the surface of the modified fiber promote heterogeneous nucleation of the regenerated polypropylene, resulting in the production of β-crystals, which promotes the absorption of high-energy particles during the radiation process, and finally prepares the polypropylene substrate.

[0011] A2. Placing the polypropylene substrate in an electron beam irradiation device to obtain cross-linked polypropylene after electron irradiation.

[0012] Reaction principle for preparing cross-linked polypropylene: During the process of high-energy radiation irradiating polypropylene, modified fibers and radiation cross-linking agents, energy materials are absorbed, resulting in the breaking of carbon-carbon double bonds to produce free reactive free radicals, which are then cross-linked by continuously polymerizing polypropylene chain segments to ultimately prepare cross-linked polypropylene.

[0013] Furthermore, in step A1, the amount ratio of cross-linked polypropylene, modified fiber and radiation cross-linking agent is 40-50g:1-3g:5-8g, the temperatures of the seven temperature zones of the twin-screw extruder from the feed port to the discharge port are 170°C, 185°C, 185°C, 200°C, 200°C, 210°C, and 210°C, respectively, the main engine speed of the twin-screw extruder is 120-160rpm, and the pressure is 80-120bar; in step A2, the operation of electron radiation is: nitrogen protection is introduced into the electron radiation device at a flow rate of 15-20L / min, and the electron beam energy is set to 3-4MeV, the power is 20-25kW, the radiation dose is 200-250kGy, and the conveyor belt speed is set to 1-3m / min.

[0014] Furthermore, the plasticizer is one or more of dioctyl phthalate, diisononyl phthalate and tributyl citrate; the stabilizer is one or two of butylated hydroxytoluene and triphenyl phosphite; the lubricant is one or more of calcium stearate, oxidized polyethylene wax and montan wax; the antioxidant is one or more of tri-tert-butyl hydroxyphenyl acrylate, tetramethyl dihydroxyphenyl acrylate and tri-tert-butyl hydroxyphenyl acrylate.

[0015] Furthermore, the preparation method of the modified fiber is: dense fiber, 4,6-divinyl-1,3,5-triazine-2-amine, 3-aminopropyltriethoxysilane, triethylamine and N,N-dimethylformamide are added to a reactor and stirred, the temperature of the reactor is increased to 80-120°C, the reaction is kept warm for 2-4 hours, and the modified fiber is obtained by post-treatment.

[0016] The reaction equation for preparing modified fiber is:

[0017] Where: Indicates dense fibers, , the asterisk indicates the connection site between R1 and the imino group on the modified fiber.

[0018] The reaction principle for preparing the modified fiber is: under the catalysis of the catalyst, a large number of carboxyl groups on the surface of the dense fiber react with 4,6-divinyl-1,3,5-triazine-2-amine and 3-aminopropyltriethoxysilane to form a structure connected by amide bonds, and finally the modified fiber is prepared.

[0019] Furthermore, the stirring rate of the reactor is 40-60rpm, the amount ratio of dense fiber, 4,6-divinyl-1,3,5-triazine-2-amine, 3-aminopropyltriethoxysilane, triethylamine and N,N-dimethylformamide is 8-10g:1-2g:2-3g:0.3-0.5g:50-60mL, and the post-treatment includes: after the reaction is completed, the temperature of the reactor is lowered to room temperature, the reaction liquid is filtered to collect the filter cake, and after washing with ethanol and deionized water for 3-5 times respectively, the filter cake is placed in a drying oven at a temperature of 80°C and vacuum dried until the filter cake has a constant weight to obtain modified fiber.

[0020] Furthermore, the preparation method of the dense fiber comprises the following steps:

[0021] B1, immersing the carbon-coated fiber in an oxidizing solution, irradiating it with an ultraviolet lamp for 1-2 hours, and post-treating it to obtain oxidized fiber;

[0022] The reaction principle of preparing oxidized fibers: Under the irradiation of ultraviolet light, the oxidizing liquid is activated to oxidize the carbon layer on the surface of the carbon-coated fiber, introducing active functional groups such as carboxyl, hydroxyl and epoxy groups on its surface, and finally preparing oxidized fibers.

[0023] B2. Add the oxidized fiber into a hot isostatic pressing furnace, increase the temperature of the hot isostatic pressing furnace to 1200-1500°C, and increase the pressure to 300-400MPa. After high temperature and high pressure treatment for 4-6 hours, dense fibers are obtained.

[0024] The reaction principle for preparing dense fibers is as follows: under high temperature, the atoms in the grain boundaries move and rearrange, which promotes the bonding between the particles. Under high pressure, the particles in the material undergo microscopic plastic deformation. The particles rearrange themselves under high temperature and high pressure conditions and fill the pores. The active functional groups endowed to the carbon layer through oxidation react under high temperature and high pressure, promoting the polymerization between materials and ultimately making the internal structure of the material denser.

[0025] Furthermore, in step B1, the oxidizing liquid is composed of 3-5wt% hydrogen peroxide and 0.1-0.5wt% potassium permanganate solution in a dosage ratio of 5-8mL:2-3mL, the wavelength of the ultraviolet lamp is 260-360nm, the dosage ratio of the carbon-coated fiber and the oxidizing liquid is 1g:3-5mL, and the post-treatment includes: after the reaction is completed, using a saturated sodium hydroxide solution to neutralize the reaction liquid until the system is neutral, filtering the reaction liquid to collect the filter cake, washing the filter cake with ethanol and deionized water for 3-5 times, and placing the filter cake in a drying oven at a temperature of 60°C and vacuum drying it until the filter cake has a constant weight to obtain oxidized fiber.

[0026] Further, the preparation method of the carbon-coated fiber is:

[0027] C1. Add silicon carbide fiber and ethanol into a reactor, ultrasonically treat for 10-20 min, then add triethylamine, N-aminoethyl-3-aminopropyltriethoxysilane and deionized water into the reactor, ultrasonically treat for 1-2 h at room temperature, and post-treat to obtain assembled fiber;

[0028] The principle of preparing assembled fibers is as follows: after washing with ethanol, active groups such as hydroxyl groups are exposed on the surface of silicon carbide. With the addition of N-aminoethyl-3-aminopropyltriethoxysilane and a catalyst, the siloxy groups on its chain segments are hydrolyzed to form silanols, which form cross-links with the surface of the silicon carbide fiber to prepare assembled fibers.

[0029] C2. Add the assembled fibers into a vapor deposition device to obtain carbon-coated fibers through vapor deposition.

[0030] The principle of preparing carbon-coated fibers is as follows: methane, as a precursor gas, decomposes under high temperature to generate free radicals and carbon atoms. These free radicals and carbon atoms will be adsorbed on the fiber surface. As the reaction proceeds, these adsorbed carbon atoms will combine on the fiber surface to form a thin and uniform carbon layer, and finally the carbon-coated fibers will be prepared.

[0031] Furthermore, in step C1, the amount ratio of silicon carbide fiber, ethanol, triethylamine, N-aminoethyl-3-aminopropyltriethoxysilane and deionized water is 8-10g:30-40mL:1-2g:3-5g:10-15mL, the ultrasonic frequency is 20-40kHz, and the post-treatment includes: after the reaction is completed, the reaction liquid is filtered to collect the filter cake, the filter cake is washed with deionized water and ethanol for 3-5 times, and the filter cake is placed in a drying oven at a temperature of 60°C for vacuum drying until the filter cake has a constant weight to obtain assembled fiber; in step C2, the vapor deposition operation is: after nitrogen is introduced to exhaust the air in the reaction chamber, the temperature of the reaction chamber is increased to 800-1200°C, the air pressure is set to 1000-1200Pa, and a mixed gas of methane and nitrogen in a volume ratio of 1-2:20 is introduced, the gas flow rate is 600-800sccm, and the heat treatment is carried out for 2-4h to obtain carbon-coated fiber.

[0032] Furthermore, the preparation method of the radiation crosslinker is: add 1,3,5,7-tetravinyl-1,3,5,7-tetramethylcyclotetrasiloxane, triallyl phosphate and ethyl acetate into a reaction kettle and stir, add the mixed solution into a spray dryer after all the solids are dissolved, and obtain the radiation crosslinker after atomization drying.

[0033] The reaction principle of preparing the radiation cross-linking agent: after the atomized droplets are dried by high-temperature air, the liquid is converted into dry powder of uniform shape and size in a short time, so that the radiation cross-linking agent finally prepared is evenly mixed.

[0034] Further, the amount ratio of 1,3,5,7-tetravinyl-1,3,5,7-tetramethylcyclotetrasiloxane, triallyl phosphate and ethyl acetate is 5-8g:3-5g:40-60mL, and the operation of atomization drying is as follows: the feed amount of the spray dryer is set to 100-500mL / h, the spray pressure is 0.5-2.0MPa, the spray is contacted with hot air at a temperature of 150-200°C, and the hot air flow rate is 1-3m 3 / h, and after drying, the powder is collected by a dust collector to obtain the radiation cross-linking agent.

[0035] The present invention also provides a method for preparing a fiber-reinforced recycled polypropylene composite material, comprising the following steps:

[0036] S1, adding cross-linked polypropylene, modified fiber, plasticizer, stabilizer, lubricant and antioxidant into a stirring tank and mixing them evenly to obtain a mixture;

[0037] S2. Add the mixed material into a twin-screw extruder and perform melt extrusion to obtain a fiber-reinforced recycled polypropylene composite material.

[0038] Furthermore, the temperatures of the seven temperature zones of the twin-screw extruder from the feed port toward the discharge port are 170°C, 185°C, 185°C, 200°C, 200°C, 210°C, and 210°C, respectively, and the main engine speed of the twin-screw extruder is 120-160rpm, and the pressure is 80-120bar.

[0039] The present invention has the following beneficial effects:

[0040] 1. In the process of preparing a fiber-reinforced recycled polypropylene composite material, the present invention first modifies silicon carbide by single-molecule self-assembly modification and carbon deposition coating to obtain a modified fiber, the surface of which has a large number of amide groups and carbon-carbon double bonds. In the process of preparing a polypropylene substrate, the amide groups on the surface promote heterogeneous nucleation of the recycled polypropylene to form a β crystal. The presence of the β crystal helps to increase the generation rate of free radicals and provide a wider reaction space, increase the possibility of cross-linking between chains, and improve the efficiency of radiation cross-linking. The carbon-carbon double bonds on the surface cooperate with the radiation cross-linking agent to further hybridize the spatial chain segments of the polypropylene, so that the wear resistance and mechanical properties of the cross-linked polypropylene are significantly improved. The phosphoric acid component in the radiation cross-linking agent decomposes during the combustion process to produce acidic substances, which promotes the carbonization of the triazine ring on the surface of the modified fiber, so that a rough carbon structure is formed on the surface of the modified fiber, and the fluidity of the combustion material is reduced. This structure cooperates with the modified carbon on the surface of the silicon carbide to significantly improve the flame retardant properties of the fiber-reinforced recycled polypropylene composite material.

[0041] 2. The present invention uses silicon carbide fibers to obtain assembled fibers through surface single-molecule self-assembly, and a large number of organic groups are aggregated on the surface of the assembled fibers. After the carbon deposition promoted by these large number of organic groups forms a uniform and tight carbon layer on the surface of the assembled fibers, the obtained carbon-coated fibers are subjected to surface oxidation to introduce a large number of active functional groups on the surface to obtain oxidized fibers. The fibers are further subjected to high temperature and high pressure conditions of hot isostatic pressing to promote the movement and rearrangement of the surface, promote the bonding between particles, and cause microscopic plastic deformation of the particles, which are rearranged under high temperature and high pressure conditions and filled into the pores. This plastic deformation not only eliminates the pores of the material, but also gradually closes the pores in the material under the action of isostatic pressing. As the temperature and pressure increase, the gas in the pores will be compressed or discharged, and the pore walls will collapse or weld, ultimately making the interior of the material densified, and a large number of active groups on its surface are activated, such as epoxy groups undergoing ring-opening reactions and reactions with hydroxyl groups to form a tighter fiber surface structure. Finally, surface branches with double bonds and amide groups are formed by reacting with monomers, while giving the modified fibers the ability of heterogeneous nucleation of β-nucleating agents and partial cross-linking agents. BRIEF DESCRIPTION OF THE DRAWINGS

[0042] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0043] Figure 1 This is a SEM image of the modified fiber prepared in Example 3 of the present invention;

[0044] Figure 2 This is a SEM image of the oxidized fiber prepared in Example 3 of the present invention. DETAILED DESCRIPTION

[0045] The technical solution of the present invention will be clearly and completely described below in conjunction with the embodiments. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0046] Example 1

[0047] This embodiment provides a method for preparing a fiber-reinforced recycled polypropylene composite material, comprising the following steps:

[0048] S1. Preparation of dense fibers

[0049] Weigh: 24.0g of silicon carbide fiber and 100.0mL of ethanol are added to a reactor, the ultrasonic frequency is 20kHz, and after ultrasonic treatment for 10min, 3.6g of triethylamine, 10.0g of N-aminoethyl-3-aminopropyltriethoxysilane and 30.0mL of deionized water are added to the reactor, and ultrasonic treatment is performed at room temperature for 1h. After the reaction is completed, the reaction liquid is filtered to collect the filter cake, and the filter cake is washed with deionized water and ethanol for 3 times, and then the filter cake is placed in a drying oven at a temperature of 60°C for vacuum drying until the filter cake has a constant weight, to obtain an assembled fiber;

[0050] The assembled fiber was added to a vapor deposition device, and after nitrogen was introduced to exhaust the air in the reaction chamber, the temperature of the reaction chamber was raised to 800°C, the gas pressure was set to 1000 Pa, and a mixed gas of methane and nitrogen in a volume ratio of 1:20 was introduced, the gas flow rate was 800 sccm, and the heat treatment was carried out for 4 hours to obtain a carbon-coated fiber;

[0051] Weigh: 15.0 mL of 3.0 wt% hydrogen peroxide and 6.0 mL of 0.3 wt% potassium permanganate solution to prepare an oxidizing solution;

[0052] Weigh: 30.0g carbon-coated fiber is immersed in 100.0mL oxidation solution, and irradiated with ultraviolet lamp for 2h, the wavelength of ultraviolet lamp is 260nm, after the reaction is completed, the reaction solution is neutralized with saturated sodium hydroxide solution until the system is neutral, the reaction solution is filtered to collect the filter cake, the filter cake is washed with ethanol and deionized water for 5 times, and the filter cake is placed in a drying oven at a temperature of 60°C and vacuum dried until the filter cake has a constant weight, to obtain oxidized fiber;

[0053] The oxidized fiber was added into a hot isostatic pressing furnace, the temperature of the hot isostatic pressing furnace was increased to 1200°C, the pressure was increased to 300MPa, and after high temperature and high pressure treatment for 4h, a dense fiber was obtained.

[0054] S2. Preparation of cross-linked polypropylene

[0055] Weigh: 30.0 g dense fiber, 3.6 g 4,6-divinyl-1,3,5-triazine-2-amine, 7.2 g 3-aminopropyltriethoxysilane, 1.2 g triethylamine and 150.0 mL N,N-dimethylformamide, add into the reactor and stir at a rate of 40 rpm, raise the temperature of the reactor to 80°C, keep warm for 2 hours, after the reaction is completed, lower the temperature of the reactor to room temperature, filter the reaction liquid to collect the filter cake, wash it with ethanol and deionized water for 3 times respectively, place the filter cake in a drying oven at 80°C and vacuum dry it until the filter cake has a constant weight, and obtain modified fiber;

[0056] Weigh: 10.0g 1,3,5,7-tetravinyl-1,3,5,7-tetramethylcyclotetrasiloxane, 6.4g triallyl phosphate and 100.0mL ethyl acetate were added to the reactor and stirred. After the solid was completely dissolved, the mixed solution was added to the spray dryer. The feed rate of the spray dryer was set to 100mL / h, the spray pressure was 0.5MPa, the spray was in contact with hot air at a temperature of 150°C, and the hot air flow rate was 1m 3 / h, after drying, use a dust collector to collect the powder to obtain a radiation cross-linking agent;

[0057] Weigh: 80.0 g of recycled polypropylene, 5.0 g of modified fiber and 12.0 g of radiation crosslinking agent, mix them evenly and add them into a twin-screw extruder, the temperatures of the seven temperature sections of the twin-screw extruder from the feed port to the discharge port are 170° C., 185° C., 185° C., 200° C., 200° C., 210° C., 210° C., the main engine speed of the twin-screw extruder is 120 rpm, the pressure is 80 bar, and the polypropylene substrate is obtained by melt extrusion;

[0058] The polypropylene substrate was placed in an electron beam irradiation device, nitrogen protection was introduced into the electron irradiation device at a flow rate of 15 L / min, and the electron beam energy was set to 3 MeV, the power was 20 kW, the radiation dose was 200 kGy, and the conveyor belt speed was set to 1 m / min. After electron irradiation, cross-linked polypropylene was obtained.

[0059] S3. Preparation of fiber-reinforced recycled polypropylene composites

[0060] Weigh: 84.0 g of cross-linked polypropylene, 16.0 g of modified fiber, 16.0 g of dioctyl phthalate, 4.8 g of butylated hydroxytoluene, 1.2 g of calcium stearate and 0.8 g of tri-tert-butyl hydroxyphenyl acrylate, add into a stirring tank and mix well to obtain a mixture;

[0061] The mixed material is added into a twin-screw extruder, and the temperatures of the seven temperature zones of the twin-screw extruder from the feed port toward the discharge port are 170°C, 185°C, 185°C, 200°C, 200°C, 210°C, and 210°C, respectively. The main engine speed of the twin-screw extruder is 120rpm, and the pressure is 80bar. The fiber-reinforced recycled polypropylene composite material is obtained by melt extrusion.

[0062] Example 2

[0063] This embodiment provides a method for preparing a fiber-reinforced recycled polypropylene composite material, comprising the following steps:

[0064] S1. Preparation of dense fibers

[0065] Weigh: 27.0g of silicon carbide fiber and 100.0mL of ethanol are added to a reactor, the ultrasonic frequency is 40kHz, and after ultrasonic treatment for 20min, 5.0g of triethylamine, 12.0g of N-aminoethyl-3-aminopropyltriethoxysilane and 30.0mL of deionized water are added to the reactor, and ultrasonic treatment is performed at room temperature for 2h. After the reaction is completed, the reaction liquid is filtered to collect the filter cake, and the filter cake is washed with deionized water and ethanol for 5 times, and then placed in a drying oven at a temperature of 60°C for vacuum drying until the filter cake has a constant weight, to obtain an assembled fiber;

[0066] The assembled fiber was added to a vapor deposition device, and after nitrogen was introduced to exhaust the air in the reaction chamber, the temperature of the reaction chamber was raised to 1200°C, the gas pressure was set to 1100 Pa, and a mixed gas of methane and nitrogen in a volume ratio of 2:20 was introduced at a gas flow rate of 600 sccm. The heat treatment was carried out for 4 hours to obtain a carbon-coated fiber;

[0067] Weigh: 20.0 mL of 4.0 wt% hydrogen peroxide and 8.0 mL of 0.4 wt% potassium permanganate solution to prepare an oxidizing solution;

[0068] Weigh: 30.0g carbon-coated fiber is immersed in 100.0mL oxidation solution, the wavelength of the ultraviolet lamp is 360nm, and the ultraviolet lamp is used for irradiation for 2h. After the reaction is completed, the reaction solution is neutralized with a saturated sodium hydroxide solution until the system is neutral, and the reaction solution is filtered to collect the filter cake. After washing the filter cake with ethanol and deionized water for 4 times, the filter cake is placed in a drying oven at a temperature of 60°C and vacuum dried until the filter cake has a constant weight to obtain oxidized fiber;

[0069] The oxidized fiber was added into a hot isostatic pressing furnace, the temperature of the hot isostatic pressing furnace was increased to 1500°C, the pressure was increased to 350MPa, and after high temperature and high pressure treatment for 6 hours, a dense fiber was obtained.

[0070] S2. Preparation of cross-linked polypropylene

[0071] Weigh: 27.0 g dense fiber, 6.0 g 4,6-divinyl-1,3,5-triazine-2-amine, 8.0 g 3-aminopropyltriethoxysilane, 1.0 g triethylamine and 150.0 mL N,N-dimethylformamide, add into the reactor and stir at a rate of 60 rpm, raise the temperature of the reactor to 100°C, keep warm for 3 hours, after the reaction is completed, lower the temperature of the reactor to room temperature, filter the reaction liquid to collect the filter cake, wash it with ethanol and deionized water for 4 times respectively, place the filter cake in a drying oven at 80°C and vacuum dry it until the filter cake has a constant weight, to obtain modified fiber;

[0072] Weigh: 16.0g 1,3,5,7-tetravinyl-1,3,5,7-tetramethylcyclotetrasiloxane, 9.0g triallyl phosphate and 84.0mL ethyl acetate are added to the reactor and stirred. After the solid is completely dissolved, the mixed solution is added to the spray dryer. The feed rate of the spray dryer is set to 500mL / h, the spray pressure is 2.0MPa, the spray is in contact with hot air at a temperature of 200°C, and the hot air flow rate is 3m 3 / h, after drying, use a dust collector to collect the powder to obtain a radiation cross-linking agent;

[0073] Weigh: 50.0 g of recycled polypropylene, 2.4 g of modified fiber and 7.2 g of radiation crosslinking agent, mix them evenly and add them into a twin-screw extruder, the temperatures of the seven temperature sections of the twin-screw extruder from the feed port to the discharge port are 170° C., 185° C., 185° C., 200° C., 200° C., 210° C., 210° C., the main engine speed of the twin-screw extruder is 160 rpm, the pressure is 120 bar, and the polypropylene substrate is obtained by melt extrusion;

[0074] The polypropylene substrate was placed in an electron beam irradiation device, nitrogen protection was introduced into the electron irradiation device at a flow rate of 20 L / min, and the electron beam energy was set to 4 MeV, the power was 25 kW, the radiation dose was 250 kGy, and the conveyor belt speed was set to 3 m / min. After electron irradiation, cross-linked polypropylene was obtained.

[0075] S3. Preparation of fiber-reinforced recycled polypropylene composites

[0076] Weigh: 96.0 g of cross-linked polypropylene, 18.0 g of modified fiber, 16.0 g of dioctyl phthalate, 4.8 g of butylated hydroxytoluene, 1.2 g of calcium stearate and 0.8 g of tri-tert-butyl hydroxyphenyl acrylate, add into a stirring tank and mix well to obtain a mixture;

[0077] The mixed material is added into a twin-screw extruder, and the temperatures of the seven temperature zones of the twin-screw extruder from the feed port toward the discharge port are 170°C, 185°C, 185°C, 200°C, 200°C, 210°C, and 210°C, respectively. The main engine speed of the twin-screw extruder is 160rpm, and the pressure is 120bar. The fiber-reinforced recycled polypropylene composite material is obtained by melt extrusion.

[0078] Example 3

[0079] This embodiment provides a method for preparing a fiber-reinforced recycled polypropylene composite material, comprising the following steps:

[0080] S1. Preparation of dense fibers

[0081] Weigh: 27.0g of silicon carbide fiber and 100.0mL of ethanol are added to a reactor, the ultrasonic frequency is 30kHz, and after ultrasonic treatment for 15min, 5.0g of triethylamine, 12.0g of N-aminoethyl-3-aminopropyltriethoxysilane and 40.0mL of deionized water are added to the reactor, and ultrasonic treatment is performed at room temperature for 2h. After the reaction is completed, the reaction liquid is filtered to collect the filter cake, and the filter cake is washed with deionized water and ethanol for 4 times, and then the filter cake is placed in a drying oven at a temperature of 60°C for vacuum drying until the filter cake has a constant weight, to obtain an assembled fiber;

[0082] The assembled fiber was added to a vapor deposition device, and after nitrogen was introduced to exhaust the air in the reaction chamber, the temperature of the reaction chamber was raised to 1000°C, the gas pressure was set to 1200 Pa, and a mixed gas of methane and nitrogen in a volume ratio of 2:20 was introduced, the gas flow rate was 800 sccm, and the heat treatment was carried out for 3 hours to obtain a carbon-coated fiber;

[0083] Weigh: 16.0 mL of 5.0 wt% hydrogen peroxide and 5.0 mL of 0.5 wt% potassium permanganate solution to prepare an oxidizing solution;

[0084] Weigh: 30.0g carbon-coated fiber is immersed in 100.0mL oxidation solution, and irradiated with ultraviolet lamp for 2h, the wavelength of ultraviolet lamp is 320nm, after the reaction is completed, the reaction solution is neutralized with saturated sodium hydroxide solution until the system is neutral, the reaction solution is filtered to collect the filter cake, the filter cake is washed with ethanol and deionized water for 4 times, and the filter cake is placed in a drying oven at a temperature of 60°C and vacuum dried until the filter cake has a constant weight, to obtain oxidized fiber;

[0085] The oxidized fiber was added into a hot isostatic pressing furnace, the temperature of the hot isostatic pressing furnace was increased to 1350°C, and the pressure was increased to 400MPa. After high temperature and high pressure treatment for 5 hours, dense fiber was obtained.

[0086] S2. Preparation of cross-linked polypropylene

[0087] Weigh: 30.0 g dense fiber, 6.0 g 4,6-divinyl-1,3,5-triazine-2-amine, 8.0 g 3-aminopropyltriethoxysilane, 1.2 g triethylamine and 200.0 mL N,N-dimethylformamide, add into the reactor and stir at a rate of 50 rpm, raise the temperature of the reactor to 100°C, keep warm for 3 hours, after the reaction is completed, lower the temperature of the reactor to room temperature, filter the reaction liquid to collect the filter cake, wash it with ethanol and deionized water for 4 times respectively, place the filter cake in a drying oven at 80°C and vacuum dry it until the filter cake has a constant weight, to obtain modified fiber;

[0088] Weigh: 14.8g 1,3,5,7-tetravinyl-1,3,5,7-tetramethylcyclotetrasiloxane, 8.4g triallyl phosphate and 80.0mL ethyl acetate, add them into the reactor and stir. After the solid is completely dissolved, add the mixed solution into the spray dryer. Set the feed rate of the spray dryer to 300mL / h, the spray pressure to 1.6MPa, and the spray is in contact with hot air at a temperature of 180°C. The hot air flow rate is 2m 3 / h, after drying, use a dust collector to collect the powder to obtain a radiation cross-linking agent;

[0089] Weigh: 50.0 g of recycled polypropylene, 3.0 g of modified fiber and 8.0 g of radiation crosslinking agent, mix them evenly and add them into a twin-screw extruder, the temperatures of the seven temperature sections of the twin-screw extruder from the feed port to the discharge port are 170° C., 185° C., 185° C., 200° C., 200° C., 210° C., 210° C., the main engine speed of the twin-screw extruder is 140 rpm, the pressure is 100 bar, and the polypropylene substrate is obtained by melt extrusion;

[0090] The polypropylene substrate was placed in an electron beam irradiation device, and nitrogen protection was introduced into the electron irradiation device at a flow rate of 18 L / min. The electron beam energy was set to 4 MeV, the power was set to 24 kW, the radiation dose was set to 225 kGy, and the conveyor belt speed was set to 2 m / min. After electron irradiation, cross-linked polypropylene was obtained.

[0091] S3. Preparation of fiber-reinforced recycled polypropylene composites

[0092] Weigh: 96.0 g of cross-linked polypropylene, 18.0 g of modified fiber, 16.0 g of dioctyl phthalate, 4.8 g of butylated hydroxytoluene, 1.2 g of calcium stearate and 0.8 g of tri-tert-butyl hydroxyphenyl acrylate, add into a stirring tank and mix well to obtain a mixture;

[0093] The mixed material is added into a twin-screw extruder, and the temperatures of the seven temperature zones of the twin-screw extruder from the feed port toward the discharge port are 170°C, 185°C, 185°C, 200°C, 200°C, 210°C, and 210°C, respectively. The main engine speed of the twin-screw extruder is 140rpm, and the pressure is 100bar. The fiber-reinforced recycled polypropylene composite material is obtained by melt extrusion.

[0094] Comparative Example 1

[0095] The difference between this comparative example and Example 3 is that the step of preparing modified fibers in step S2 is eliminated, and in the process of preparing cross-linked polypropylene, an equal amount of dense fibers is used to replace the modified fibers.

[0096] Comparative Example 2

[0097] The difference between this comparative example and Example 3 is that in the process of preparing cross-linked polypropylene in step S2, the use of modified fiber is eliminated.

[0098] Comparative Example 3

[0099] The difference between this comparative example and Example 3 is that in the process of preparing cross-linked polypropylene in step S2, the radiation cross-linking agent is eliminated.

[0100] Performance Test:

[0101] The limiting oxygen index of the fiber-reinforced recycled polypropylene composites prepared in Examples 1-3 and Comparative Examples 1-3 was tested with reference to the standard GB / T 2406.2-2009 "Determination of Combustion Behavior of Plastics by Oxygen Index Method Part 2: Room Temperature Test";

[0102] The volume wear of the fiber-reinforced recycled polypropylene composite materials prepared in Examples 1-3 and Comparative Examples 1-3 was tested with reference to the standard GB / T 9867-2008 "Determination of wear resistance of vulcanized rubber or thermoplastic rubber (rotating roller abrader method)";

[0103] The vertical burning rating of the fiber-reinforced recycled polypropylene composite materials prepared in Examples 1-3 and Comparative Examples 1-3 was tested with reference to the standard GB / T 26526-2011 "Specification for Thermoplastic Elastomer Low-Smoke Halogen-Free Flame Retardant Materials";

[0104] The tensile strength of the fiber-reinforced recycled polypropylene composite materials prepared in Examples 1-3 and Comparative Examples 1-3 was tested with reference to the standard GB / T 528-2009 “Determination of tensile stress-strain properties of vulcanized rubber or thermoplastic rubber”. The specific data are shown in Table 1.

[0105] Table 1-Performance test data of each sample

[0106] Data Analysis:

[0107] Comparative analysis of the data in Table 1 above shows that the fiber-reinforced recycled polypropylene composite material prepared by the present invention has a limiting oxygen index of 39.5% and a volume wear loss of 29 mm. 3 , the vertical combustion grade is V-0 and the tensile strength reaches 92.1MPa, which fully demonstrates that:

[0108] In the process of preparing a fiber-reinforced recycled polypropylene composite material, the present invention first modifies silicon carbide by single-molecule self-assembly modification and carbon deposition coating to obtain a modified fiber, the surface of which has a large number of amide groups and carbon-carbon double bonds. In the process of preparing a polypropylene substrate, the amide groups on the surface promote heterogeneous nucleation of the recycled polypropylene to form a β crystal form. The existence of the β crystal form helps to improve the generation rate of free radicals, and provides a wider reaction space, increases the possibility of cross-linking between chains, thereby improving the radiation cross-linking efficiency. The carbon-carbon double bonds on the surface cooperate with the radiation cross-linking agent to further hybridize the spatial chain segments of the polypropylene, so that the wear resistance and mechanical properties of the cross-linked polypropylene are significantly improved. The phosphoric acid component in the modified cross-linking agent is decomposed in the combustion process to generate acidic substances, which promotes the carbonization of the triazine ring on the surface of the modified fiber, so that a rough carbon structure is formed on the surface of the modified fiber. The structure cooperates with the modified carbon on the surface of the silicon carbide to significantly improve the flame retardant property of the fiber-reinforced recycled polypropylene composite material.

[0109] The preferred embodiments of the present invention disclosed above are only used to help explain the present invention. The preferred embodiments do not describe all the details in detail, nor do they limit the invention to only specific implementation methods. Obviously, many modifications and changes can be made according to the content of this specification. This specification selects and specifically describes these embodiments in order to better explain the principles and practical applications of the present invention, so that those skilled in the art can understand and use the present invention well. The present invention is limited only by the claims and their full scope and equivalents.

Claims

1. A fiber-reinforced recycled polypropylene composite material, characterized in that: The invention comprises the following raw materials by weight: 80-100 parts of cross-linked polypropylene, 10-20 parts of modified fiber, 10-20 parts of plasticizer, 2-5 parts of stabilizer, 0.5-2 parts of lubricant and 0.5-1 parts of antioxidant; Wherein, the preparation method of cross-linked polypropylene comprises the following steps: A1, mixing recycled polypropylene, modified fiber and radiation crosslinking agent uniformly and adding them into a twin-screw extruder, and melt-extrude to obtain a polypropylene substrate; A2. Placing the polypropylene substrate in an electron beam irradiation device to obtain cross-linked polypropylene after electron irradiation.

2. The fiber-reinforced recycled polypropylene composite material according to claim 1, characterized in that: In step A1, the amount ratio of recycled polypropylene, modified fiber and radiation crosslinking agent is 40-50g:1-3g:5-8g, the temperature of the seven temperature sections of the twin-screw extruder from the feed port to the discharge port is 170°C, 185°C, 185°C, 200°C, 200°C, 210°C, 210°C, the main engine speed of the twin-screw extruder is 120-160rpm, and the pressure is 80-120bar; in step A2, the operation of electron radiation is: nitrogen protection is introduced into the ionizing radiation device at a flow rate of 15-20L / min, and the electron beam energy is set to 3-4MeV, the power is 20-25kW, the radiation dose is 200-250kGy, and the conveyor belt speed is set to 1-3m / min.

3. The fiber-reinforced recycled polypropylene composite material according to claim 1, characterized in that: The preparation method of the modified fiber is as follows: dense fiber, 4,6-divinyl-1,3,5-triazine-2-amine, 3-aminopropyltriethoxysilane, triethylamine and N,N-dimethylformamide are added into a reaction kettle and stirred, the temperature of the reaction kettle is increased to 80-120° C., the reaction is kept warm for 2-4 hours, and the modified fiber is obtained by post-processing.

4. The fiber-reinforced recycled polypropylene composite material according to claim 3, characterized in that: The stirring rate of the reaction kettle is 40-60 rpm, and the dosage ratio of dense fiber, 4,6-divinyl-1,3,5-triazine-2-amine, 3-aminopropyltriethoxysilane, triethylamine and N,N-dimethylformamide is 8-10 g: 1-2 g: 2-3 g: 0.3-0.5 g: 50-60 mL.

5. The fiber-reinforced recycled polypropylene composite material according to claim 3, characterized in that: The preparation method of the dense fiber comprises the following steps: B1, immersing the carbon-coated fiber in an oxidizing solution, irradiating it with an ultraviolet lamp for 1-2 hours, and post-treating it to obtain oxidized fiber; B2. Add the oxidized fiber into a hot isostatic pressing furnace, increase the temperature of the hot isostatic pressing furnace to 1200-1500°C, and increase the pressure to 300-400MPa. After high temperature and high pressure treatment for 4-6 hours, dense fibers are obtained.

6. The fiber-reinforced recycled polypropylene composite material according to claim 5, characterized in that: In step B1, the oxidizing solution is composed of 3-5wt% hydrogen peroxide and 0.1-0.5wt% potassium permanganate solution in a dosage ratio of 5-8mL:2-3mL, the wavelength of the ultraviolet lamp is 260-360nm, and the dosage ratio of carbon-coated fiber to oxidizing solution is 1g:3-5mL.

7. The fiber-reinforced recycled polypropylene composite material according to claim 5, characterized in that: The preparation method of the carbon-coated fiber is as follows: C1. Add silicon carbide fiber and ethanol into a reactor, ultrasonically treat for 10-20 min, then add triethylamine, N-aminoethyl-3-aminopropyltriethoxysilane and deionized water into the reactor, ultrasonically treat for 1-2 h at room temperature, and post-treat to obtain assembled fiber; C2. Add the assembled fibers into a vapor deposition device to obtain carbon-coated fibers through vapor deposition.

8. The fiber-reinforced recycled polypropylene composite material according to claim 7, characterized in that: In step C1, the amount ratio of silicon carbide fiber, ethanol, triethylamine, N-aminoethyl-3-aminopropyltriethoxysilane and deionized water is 8-10g:30-40mL:1-2g:3-5g:10-15mL, and the ultrasonic frequency is 20-40kHz; in step C2, the vapor deposition operation is: after nitrogen is introduced to exhaust the air in the reaction chamber, the temperature of the reaction chamber is increased to 800-1200°C, the air pressure is set to 1000-1200Pa, and a mixed gas of methane and nitrogen in a volume ratio of 1-2:20 is introduced, the gas flow rate is 600-800sccm, and the heat treatment is carried out for 2-4h to obtain carbon-coated fibers.

9. The fiber-reinforced recycled polypropylene composite material according to claim 1, characterized in that: The preparation method of the radiation crosslinking agent is as follows: 1,3,5,7-tetravinyl-1,3,5,7-tetramethylcyclotetrasiloxane, triallyl phosphate and ethyl acetate are added to a reaction kettle and stirred, and after all the solids are dissolved, the mixed solution is added to a spray dryer, and the radiation crosslinking agent is obtained after atomization drying.

10. The method for preparing a fiber-reinforced recycled polypropylene composite material according to any one of claims 1 to 9, characterized in that: The following steps are involved: S1, adding cross-linked polypropylene, modified fiber, plasticizer, stabilizer, lubricant and antioxidant into a stirring tank and mixing them evenly to obtain a mixture; S2. Add the mixed material into a twin-screw extruder and perform melt extrusion to obtain a fiber-reinforced recycled polypropylene composite material.

Citation Information

Patent Citations

  • Long glass fiber reinforced regenerated polypropylene material with characteristic of low volatile organic matters and preparation method of long glass fiber reinforced regenerated polypropylene material

    CN116218075A

  • Preparation method of silicon carbide fiber reinforced silicon carbide composite material

    CN102276279A

  • High-flame-retarding composition material for new energy automobile and preparation method thereof

    CN109306187A

  • Foamed polypropylene material reinforced by modified carbon fibers and preparation method of foamed polypropylene material

    CN116836449A

  • Corrosion-resistant and anti-aging PP rope for submarine cable and production process of corrosion-resistant and anti-aging PP rope

    CN118812960A

Cited By

  • Modified polypropylene diaphragm and lithium battery diaphragm

    CN121238155A

  • A modified polypropylene separator, lithium battery separator

    CN121238155B